2011
DOI: 10.1007/s10552-011-9862-0
|View full text |Cite
|
Sign up to set email alerts
|

Sun protective behaviors and vitamin D levels in the US population: NHANES 2003–2006

Abstract: Background Sun protection is recommended for skin cancer prevention, yet little is known about the role of sun protection on vitamin D levels. Our aim was to investigate the relationship between different types of sun protective behaviors and serum 25(OH)D levels in the general US population. Methods Cross-sectional, nationally representative survey of 5,920 adults aged 18–60 years in the US National Health and Nutrition Examination Survey 2003–2006. We analyzed questionnaire responses on sun protective beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 37 publications
6
77
1
3
Order By: Relevance
“…A plausible explanation for this, despite farmers' high degree of outdoor work, might be that farmers have a more sun-protective behaviour. In a nationally representative sample of almost 6,000 adult US inhabitants, sun protective behaviours, such as staying in the shade and wearing long sleeve clothing, were associated with lower vitamin D levels [39]. This type of sun avoidance in everyday life is typical of Swedish traditional family farmers included in the cohort (personal knowledge).…”
Section: Resultsmentioning
confidence: 90%
“…A plausible explanation for this, despite farmers' high degree of outdoor work, might be that farmers have a more sun-protective behaviour. In a nationally representative sample of almost 6,000 adult US inhabitants, sun protective behaviours, such as staying in the shade and wearing long sleeve clothing, were associated with lower vitamin D levels [39]. This type of sun avoidance in everyday life is typical of Swedish traditional family farmers included in the cohort (personal knowledge).…”
Section: Resultsmentioning
confidence: 90%
“…44 In South Africa, the Mediterranean and other sun-rich areas the relevance of this study may not be immediately apparent. While individuals in sun-rich areas may be at less risk, 45 a number of studies have shown a significant prevalence of vitamin D deficiency in these areas, 46,47 potentially due to an individual's skin colour or sunscreen application. Our study findings would support the assertion that clinicians in any geographical area with a significant population of dark-skinned individuals should be mindful of the possibility of vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, only 56% of Caucasian North Americans report moderate or frequent use of sunscreen when outside on a sunny day. 9 Routine use of sunscreen significantly reduces the incidence of SCC and actinic keratoses (AKs), a class of premalignant lesions that are common precursors of SCCs. [10][11][12] Some of the clearest data on the benefits of UV protection can be found in studies of organ transplant recipients (OTRs), who experience long-term immunosuppression and are particularly susceptible to NMSCs, which can be highly aggressive in these patients.…”
Section: "I Rarely Bother With Sunscreen"mentioning
confidence: 99%